Transmission and Pattern of Spread of Chilli Veinal Mottle Virus by Aphis Gossypii Glover (Homoptera: Aphididae) - Lee, Kue Moi (1992)

(untitled)
Chilli veinal mottle virus (CVMV) is a serious problem and has become a major limiting factor in growing and production of chilli in Malaysia. This virus is transmitted non-persistently by aphid, Aphis gossypii. CVMV control efforts have been unsuccessful due to lack of knowledge on the epidemiology of the virus. S tudies on transmission and spread of CVMV to chilli using nymphs and adults of A. gossypii were conducted in the laboratory and glasshouse. Aphids and test plants (Capsicum annuumcv. Me 4) were A single A . gossypii was abl e to transmit and r e tain CVMV regardless whether it was fed or starved. A. gossypii lost CVMV infectivity more rapidly in serial transfer (when feeding) than in post- acquisition starvation (when starving). Transmission level decreased as the period of serial transfer (0-60 min) and post-acquisition starvation time (1-120 min) increased, however, the level of transmission increased with aphid density. cultured and maintained in insect proof glasshouse. Fifteen seconds and thirty seconds acquisition feeding time were found to be the optimum time for A. gossypii to transmit CVMV. All aphid forms were equally efficient in CVMV transmission.Colony establishment of A. gossypii was faster when aphids were initially released on healthy plants than on CVMV infected plants. Apterous vectors spread CVMV more efficiently than alate vectors. However, CVMV s pread faster when A. gossypii was placed on the inoculum source. Apterous adults released near the inoculum source achieved the highest level of transmission compared with the alates. In the beginning, CVMV spread occurred mostly near the inoculum source and moved outward thereafter.